La presencia de la naturaleza en la Pítica I de Píndaro (Iter, 2022)
In Píndaro’s First Pythian ode, the presence of becomes relevant on the first twotriads. The ode begins with the description of the queen of birds, who remains underthe spell of the lyre and the dance, as in a reverie. From above, the bird remainslethargic on the scepter of Zeus, as a symbol of the sublime and contemplates, at acertain distance, the world of human beings. As a metaphor for the poet, the queenpersonifies the vast expertise that has traced the creator to unforeseen horizons. Ifthe eagle represents the poet, he has an omniscient, supernatural and, undoubtedly,chosen look, about everything he will say in relation to the tyranny of Hiero. From the celestial end that this first image presents, the primary narrator takesus to the depths of the earth, the domain of the Titan Typhoon, the last and the mostobstinate enemy of Zeus. We will see how Pindar manages to capture the image ofHiero from Siracusa, recognized for his despotism without betraying his own statusas a great poet.
Keywords: Pindar - Pythian First Ode - Hiero from Siracusa - Nature